Coping With Crisis: Green Space Use in Helsinki Before and During the COVID-19 Pandemic - Korpilo, Silviya; Kajosaari, Anna; Rinne, Tiina; Hasanzadeh, Kamyar; Raymond, Christopher M.; Kyttä, Marketta (Frontiers in Sustainable Cities, 2021)
The COVID-19 pandemic has encouraged a deeper exploration about how people deal with crisis. This paper presents one of the first pre- and during-pandemic assessments of urban green infrastructure (UGI) use across the same individuals with the aim of better understanding how people's use of different types of urban green and blue spaces changed during the pandemic. A baseline Public Participation GIS survey (N = 1,583 respondents) conducted in August 2018 was followed up in May 2020 (N = 418 identical respondents) during the COVID-19 pandemic in Helsinki, Finland. We found that residents were more likely to visit UGI closer to their home during the pandemic compared with before the pandemic. Patterns of use of UGI were associated with the quality of residential green areas, for example, people sought out forests nearby one's domicile and tended to avoid parks and recreation areas in order to escape the pressures of lockdown, socially distance and avoid overcrowding. However, spatial cluster analyses also revealed that the places mapped by intensive users of natural recreational areas and more outdoor oriented users became more dispersed during the pandemic, suggesting their active search for new types of UGI, including use of agricultural land and residential areas with high tree density cover. Our results further highlighted that some types of UGI such as more distant natural and semi-natural areas and blue spaces serve as critical infrastructure both before and during the pandemic. Natural and semi-natural areas experienced very little change in use. The presented results have implications for how planners design and manage green spaces to enable residents to cope with crises like pandemics into the future.